Pengembangan Media Pendidikan Kesehatan Berbasis Seni Budaya Banjar Madihin Dalam Pencegahan Perilaku Merokok Pada Remaja - Taufik Hidayat; Any Zahrotul Widniah; Hananya Gian (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Smoking behavior among adolescents remains a significant public health issue in Indonesia, particularly due to early initiation during school age. This community service activity aimed to improve knowledge and attitudes related to smoking prevention through culturally based health education using Banjar traditional art (madihin). The method employed a pre-experimental design with a one-group pretest-posttest approach involving 30 elementary school students. The intervention was delivered through audio-visual media incorporating local cultural elements. Data were collected using structured questionnaires measuring knowledge and attitudes before and after the intervention. The results showed an increase in mean knowledge scores from 18.67 to 19.33 (p = 0.005) and attitude scores from 32.40 to 32.57 (p = 0.000), indicating statistically significant improvements. These findings suggest that culturally adapted health education is effective in enhancing cognitive and affective aspects of smoking prevention behavior. The integration of local cultural approaches can strengthen message acceptance and promote sustainable health behavior change among children.